Characterizing Airborne Phthalate Concentrations and Dynamics in a Normally Occupied Residence - Lunderberg, David M; Kristensen, Kasper; Liu, YingJun; Misztal, Pawel K.; Tian, Yilin; Arata, Caleb; Wernis, Rebecca; Kreisberg, Nathan; Nazaroff, William W.; Goldstein, Allen H (Environmental Science & Technology, 2019)
Phthalate esters, commonly used as plasticizers, can be found indoors in the gas phase, in airborne particulate matter, in dust, and on surfaces. The dynamic behavior of phthalates indoors is not fully understood. In this study, time-resolved measurements of airborne phthalate concentrations and associated gas-particle partitioning data were acquired in a normally occupied residence. The vapor pressure and associated gas-particle partitioning of measured phthalates influenced their airborne dynamic behavior. Concentrations of higher vapor pressure phthalates correlated well with indoor temperature, with little discernible influence from direct occupant activity. Conversely, occupant-related behaviors substantially influenced the concentrations and dynamic behavior of a lower vapor pressure compound, diethylhexyl phthalate (DEHP), mainly through production of particulate matter during cooking events. The proportion of airborne DEHP in the particle phase was experimentally observed to increase under higher particle mass concentrations and lower indoor temperatures in correspondence with theory. Experimental observations indicate that indoor surfaces of the residence are large reservoirs of phthalates. The results also indicate that two key factors influenced by human behavior—temperature and particle mass concentration—cause short-term changes in airborne phthalate concentrations.